Mainstreaming gender dimension in water management for food security and food safety, country paper: Egypt - Aboul-Fotoh N.Z.; Abdin A.E.; Salem S.A. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
The current study investigates the important role of women in water management from different perspectives towards food security and food safety. Specifically, this role is analyzed through women's participation in food consumption and production in relation to irrigation water management. In addition, women's role in food distribution and processing is also presented through their responsibility for food waste. On the other hand, the current constraints of rural women to participate more actively in water management towards food security and food safety are profoundly identified. The results of the current study showed that women are currently participating in water management through various activities, although they are currently facing some social, political, educational, economical, cultural, health and institutional obstacles. Therefore, the current study has listed some recommendations to improve women's water management capabilities and capacities towards better sustainable food security and food safety.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)